Kajian Berbagai Faktor yang Memengaruhi Kualitas Laba (Studi Empiris pada Perusahaan Terindeks Kompas 100) - Febriana Louw (MABIS, 2022)
Earnings quality reflects the ability of the earnings to provide an overview of the results of a company's performance. Therefore, this study aims to determine the effect of accounting conservatism, leverage, earnings persistence, and operating cash flow volatility on earnings quality which is measured by discretionary accruals. The research population comprised of 165 companies indexed by Kompas100 on the Indonesia Stock Exchange during the period 2015 to 2019. The research sample consisted of fifty companies selected from the total population using purposive sampling technique. The collected data was subjected to descriptive statistical analysis, classical assumption test, correlation analysis, coefficient of determination, F test and t test, which was tested and processed by using a tool in the form of Statistical Product and Service Solutions (SPSS) software version 21. The data analysis technique was multiple linear regression. The results reveal that the accounting conservatism, earnings persistence, and operating cash flow volatility have a positive effect on earnings quality, while the leverage has no effect on earnings quality in companies indexed by Kompas100 on the IDX during the 2015-2019 period.Keywords:     accounting conservatism, earnings persistence, earnings quality, leverage, operating cash flow volatility